Evaluation of optimal culture conditions for marine benthic diatom Halamphora coffeaeformis growth and its biochemical properties - Baharuddin, Ninie Diana; Mohamed Ramli, Norulhuda; Ghazali, Nurarina Ayuni; Tan, Hui Teng; Khaw, Yam Sim; Natrah, I. (Elsevier, 2024)
Halamphora coffeaeformis is a benthic diatom that exhibits a high-value biochemical composition and can be harnessed for various applications particularly in aquaculture. Despite its potential, significant challenges persist in the optimization of cultivation parameters and scaling up to mass cultivation level. Thus, this study aimed to identify the most suitable substrate, as well as the optimal light intensity, photoperiod, salinity, and pH for the growth of H. coffeaeformis. The biochemical composition of mass-cultured H. coffeaeformis was also analyzed. The findings revealed that polyvinyl chloride (PVC) substrates substantially outperformed bamboo by yielding significantly higher (p < 0.05) growth performance. The maximum specific growth rate (SGR) of H. coffeaeformis was recorded under the following conditions: the light intensity of 120 μmol m−2 s−1 with an 18: 6 h light/dark cycle (0.200 day−1), the salinity of 30 ppt (0.161 day−1) and the pH of 9 (0.409 day−1). Under these optimized conditions, the mass culture of H. coffeaeformis at 100 L exhibited the highest ash content (38.47 ± 0.17 % dry weight (DW)), followed by crude protein (26.26 ± 0.56 % DW) containing high-quality amino acids, carbohydrates (20.96 ± 0.81 % DW) and crude lipids (4.46 ± 0.56 % DW). The lipid profile was particularly notable for its high saturated fatty acid (SFA) content and sufficient levels of polyunsaturated fatty acids (PUFA), while maintaining the lowest fiber content (0.07 ± 0.01 % DW). These findings underscore the potential of H. coffeaeformis for large-scale aquaculture applications and highlight the importance of fine-tuning cultivation parameters to maximize its biochemical yields.